Production of reactive oxygen species by neutrophils and macrophages of F1 hybrid mice (C57Bl6xCBA) in response to stimulation with cucurbit(n)urils (n = 6, 7, 8) - A. A. Aktanova; E. A. Pashkina; O. S. Boeva; N. A. Feofanova; V. A. Kozlov (Acta Biomedica Scientifica, 2022)
Background. Due to their very small size, nanomaterials, in particular cucurbiturils, have unique physical and chemical properties that find their application in medicine. However, the toxicity of cucurbiturils is not fully understood; in particular, we are interested in the immunological safety of their use. One of the mechanisms of nanotoxicity is the formation of reactive oxygen species (ROS) by macrophages and neutrophils. Hyperproduction of ROS can lead to oxidative stress and further damage to cell DNA with loss of physiological function and development of pathology.   The aim. Evaluation of the effect of cucurbit[n]urils (n = 6, 7, 8) on the production of reactive oxygen species by mice macrophages and neutrophils.   Materials and methods. F1 hybrid mice (CBAxC57Bl/6) aged 2 months (n = 11) were used in the work. Evaluation of superoxide radical production by peritoneal mouse neutrophils and macrophages was carried out by spectrophotometric method for determining the reduction of p-nitroblue tetrazolium (NBT) to formazan.   Results. It was shown that CB[6] and CB[7] at concentrations of 0.5 and 0.3 mM do not have an inhibitory effect on ROS synthesis, but, on the contrary, significantly increase ROS production by macrophages. In addition, CB[6] 0.3 mM increases the level of ROS in neutrophils.   Conclusion. Cucurbiturils can lead to an increase in the production of ROS in immunocompetent cells, depending on the concentration used (0.3 mM and higher).